Sanção e proteção no senado brasileiro: uma análise das condições de transgressão às leis, de sua sanção ou de seu acobertamento - Santos, Natalia Navarro dos (2015)
Since the recent strengthening of the preventive polices against corruption and the development and coverage of an investigative journalism in corruption cases, the issue has become a focal concern in the Brazilian citizen routine. The advances made, reflect not just the concern about the effects of corruption imposed on the public administration organizations, and on the citizens, but also regarding the legitimacy of the political system. Nevertheless, the corruption is a hidden phenomenon and therefore we do not know enough about the current conditions of the occurrence in this illegal market. The disgruntled citizen claims from the institutions the sanction of the involved in this market. The population's perception about the degree of punitive regulatory agencies is still insufficient. In this sense, it is necessary to know the configurations that trigger the sanction and not sanction legislators involved in corruption. In order to understand if, in fact, there was leniency or not in the conduction of investigative and punitive processes. Thus, this study aims to understand what factors triggered the occurrence of sanctions in corruptions cases, likewise as the conditions which trigger the impasse between the collective act (protecting the accused and consequently protecting the network of involved) in different cases. The cases adopted were: 1) the overpricing of the TRT-SP headquarters' building; 2) the establishment and operation of an illegal gambling market in the State of Goiás and; 3) the editing and not publication of administrative acts in the Senate. I propose a comparative qualitative analysis of the cases using the configurational method. The results presented in this study, do not intend to explain every case of corruption, but contribute to the debate of the subject.